A Closer Look on Linguistic Politeness among Bugis Youth: Tabék in Situational and Philosophical Context - Gusnawaty, Gusnawaty; Lukman, Lukman; Nurwati, Andi (REiLA : Journal of Research and Innovation in Language, 2022)
With a more globalized society, the use of politeness language, especially among youths, has been considered in jeopardy. However, the understanding of whether or not the youths are still acknowledging and exercising politeness in their language use is still tiny. This matter is due to a lack of study investigating the politeness language among youths. This study aims to find the politeness formula and speech patterns for three different situational contexts: asking for help, asking for information, and rebuking in the Bugis language. This study uses a mixed quantitative-qualitative method and random sampling to gather 20 youths aged 11 to 21 as participants. The instrument used for the experiment is the Discourse Completion Test to collect the utterances. Data utterances were coded and then analyzed using a concordance and cluster-N-Gram features in the AntConc 3.5.8 application to find the sentence pattern variations with the Bugis word tabék. Interpretation of the data uses the theories of Brown & Levinson (1987), Leech (2014), Watts (2003), and Darwis (1995). The analysis revealed (1) the tabék politeness formula as a polite sign at the beginning of their speech in all situational contexts and to clarify their intentions. (2) There are several sentence patterns used by the Bugis youths for each situational context; six patterns in asking for help, five patterns in asking for information, and eight patterns in rebuking. This finding shows that Bugis youths still understand the philosophy of politeness in their socio-cultural interactions, namely sipakatau (mutual humanizing), sipakaraja (mutual respect), and sipakalebbi (mutual glorification) through various politeness strategies.